Micro and Macro Anatomical Study of Duodenum of Cari Shyama and Vanaraja Breeds of Poultry - Jain, Payal; Ingole, S. P.; Chourasia, Durga (Indian Journal of Veterinary Anatomy, 2016)
The tissue samples of duodenum for the present study were collected from birds of three different age groups (chicks, growers and layers) of Vanaraja and CARI Shyama breeds of poultry.Length of duodenum was comparatively more in chicks and growers of Vanaraja and layers of CARI Shyama. Diameter of duodenum was significantly higher in chicks of CARI Shyama and growers of Vanaraja. In chicks, the villi were short sessile to tall leaf shaped, but in other two groups villi were narrow, tall and finger shaped. Height of villi ranged between 200- 260 Î¼m in chicks and 300-1200 Î¼m in growers and layers. Glands were more in layers of CARI Shyama.